Features Of The Dysfunctionality Of Youth Socialization Institutions In The Context Of The Modern Society Development: Socio-Philosophical Analysis - Литовченко, І. В.; Королюк, К. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
Introduction. The paper studies the point and the concept meaning of dysfunctional social institutions and conducts the socio-philosophical analysis of the youth social institutions function peculiarities in Ukrainian modern society development. Social institutions dysfunction is conditioned by Ukrainian society transformation process, including globalization also, which are designated on soul searching, changing attitudinal views and interests. Social institution is the peculiar form of human activity based on clearly defined ideology, rules and disciplines system and ,also, developed social control of their implementation. The main purpose of the social institution is to satisfy social needs. The aim and tasks. The aim of the article is to explore the socio-philosophical understanding of social institutions dysfunction in the socialization processes and occurring manifestations of deviant behavior in young people in Ukrainian modern development. Research methods. The main methodological ways of study of social institutions dysfunction are socio-cultural and system approaches, structual and functional method and theoretical analysis. Research results. The historical origins of the research understanding of social institutions were found in A. Comte’s and H. Spencer’s studies. Socialization process peculiarities and human deviancy, which are conditioned with social factors, are considered in A. Burgess, E. Hoffmann’s, E. Durkheim’s, L. Coser’s, A. Cohen’s, R. McKay’s, R. Merton’s, E. Sutherland’s, T. Shibutani’s, C. Show’s studies and etc. Discussion. Nowadays, youth socialization is taking place in quite complex conditions, especially the process of social and economic inequality and crisis of the main socialization institutions such as family, school, reference groups and mass media, etc. In a result, the problems appear and become more and more extended. For example: increasing level of violence, drug and alcohol addiction, gambling, unemployment among young people and also social orphanhood and homelessness. The state of Ukrainian modern society deprives the young people of certain valuable searching, behavior rules and disciplines and it can be the reason of deviation. The pecularities of social institutions dysfunction in Ukrainian modern development can be conditioned with the factors such as negative attitude to the family and domestic surrounding, transformation changes and imperfection of education system, morality problem in mass media and etc. Conclusions. Ukrainian modern society is characterized by certain combination of deviated factors. For example: anomie, differentiation of the population, social disruption and marginality of certain social groups. All these things generate the demand of scientific and practical studies of youth socialization.